2010
DOI: 10.2340/00015555-0977
|View full text |Cite
|
Sign up to set email alerts
|

Severe Pneumonia Caused by Combined Infection with Pneumocystis jiroveci, Parainfluenza Virus Type 3, Cytomegalovirus, and Aspergillus fumigatus in a Patient with Stevens-Johnson Syndrome/toxic Epidermal Necrolysis

Abstract: Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are severe adverse cutaneous reactions to drugs. We report here the first case of severe pneumonia caused by an unusual combined infection with Pneumocystis carinii (jiroveci), parainfluenza virus type 3, cytomegalovirus and Aspergillus fumigatus in a 63-year-old female patient with allopurinol-induced SJS/TEN overlap syndrome. Following treatment with high-dose systemic corticosteroids and intravenous immunoglobulin for SJS/TEN, her mucocutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Therefore, physicians should always consider the potential roles of drugs taken even within a few days before the onset of symptoms onset when attempting to identify the agent responsible for either SJS or TEN. The fact that our first patient had a previous history of mild hypersensitivity to acetaminophen suggests that a more rapid response may occur upon re-challenge with a drug [5, 7]. However, in the second case, there was no previous history of drug hypersensitivity.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Therefore, physicians should always consider the potential roles of drugs taken even within a few days before the onset of symptoms onset when attempting to identify the agent responsible for either SJS or TEN. The fact that our first patient had a previous history of mild hypersensitivity to acetaminophen suggests that a more rapid response may occur upon re-challenge with a drug [5, 7]. However, in the second case, there was no previous history of drug hypersensitivity.…”
Section: Discussionmentioning
confidence: 91%
“…Both SJS and TEN are uncommon and life-threatening severe cutaneous adverse reactions most frequently caused by exposure to drugs [5]. One study reported that ingestion of acetaminophen was implicated in 48 of 245 patients with suspected SJS and TEN [6].…”
Section: Introductionmentioning
confidence: 99%
“…Coinfection with P. jirovecii and A. fumigatus has been reported as a complication in patients admitted to the ICU because of acute respiratory failure. Nevertheless, worldwide up to now, only a few cases of documented coinfection of PcP and IPA have been published [8,9,10,11,15,16], and one case of a patient with IPA following PcP [17]. …”
Section: Discussionmentioning
confidence: 99%
“…Up to now only a few cases of coinfection of PcP and IPA have been documented [8,9,10,11]. To capture similar cases and relevant studies we performed a systematic electronic search of the literature in PubMed with the keywords: aspergillosis, pneumocystis, coinfection.…”
Section: Introductionmentioning
confidence: 99%
“…Immuno histochemistry images confirmed acute involvement of HCMV and epidermal degeneration. The skin is the initial site of HCMV involvement (visceral disease) and may provide the first clue to systemic infection [17]. A wide spectrum of cutaneous lesions associated with HCMV infection has been reported, including purpura, morbilliform eruptions, lesions, papular eruptions, verrucous and vesiculobullous lesions, ulcerations etc.…”
Section: Immunological Parameters In Patients With Hcmv Associated Sjmentioning
confidence: 99%